PERAN GURU DAN PENDIDIK DALAM MENUMBUHKAN LITERASI DIGITAL DAN MENDUKUNG PEMBANGUNAN BERKELANJUTAN - Sihombing, Adi Putra; Rahardjo, Rafly Syamsa; Rachman, Ichsan Fauzi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Competency is a skill that educators must have in carrying out their responsibilities. In this digital age, teachers need to master various methods and media related to digital in learning. Students who are proactive and agile in following technological developments are a challenge for teachers if they are unable to utilize technology in learning. Therefore, in this modern era, teaching staff need digital competence to achieve productive and optimal learning outcomes. This research uses a descriptive qualitative approach method by accumulating reference sources. The focus of this research is to explain the digital skills that educators must have. In conclusion, in achieving success in learning activities in the modern era, it is very essential for teachers to have digital skills as an approach to responding to learning challenges in the digital era.